Building a Dynamic Social Community with Non Playable Characters - Perrie, Justin; Li, Ling (Denshi Jouhou Tsuushin Gakkai, 2014)
A challenge faced by the video game industry is to develop be-lievable and more intelligent Non-Playable Characters (NPCs). To tackle this problem a low-cost and simple ap-proach has been proposed in this research, which is the devel-opment of a gossip virtual social network for NPCs. The net-work allows simple individual NPCs to communicate their knowledge amongst themselves. The communication within this social network is governed by social-psychological rules. These rules are categorized into four types: Contact, whether the NPC are within a contactable range of each other; Obser-vation, whether the NPCs actually want to talk to each other based on their personal traits; Status, the current representa-tion of the NPCs; and Relationships which determines the long term ties of the NPCs. Evaluations of the proposed gos-sip virtual social network was conducted, both through statis-tical analysis and a survey of real users. Highly satisfactory results have been achieved.